Effect of Biostimulant Formulation on Yield, Quality, and Nitrate Accumulation in Diplotaxis tenuifolia Cultivars Under Different Weather Conditions - Alessio Vincenzo Tallarita; Rachael Simister; Lorenzo Vecchietti; Eugenio Cozzolino; Vasile Stoleru; Otilia Cristina Murariu; Roberto Maiello; Giuseppe Cozzolino; Stefania De Pascale; Gianluca Caruso (Applied Sciences)
Perennial wall rocket (Diplotaxis tenuifolia L.—DC.) exhibits genotype-dependent responses to biostimulant applications, which have not yet been deeply investigated. A two-year greenhouse factorial experiment was carried out to assess the interactions between five cultivars (Mars, Naples, Tricia, Venice, and Olivetta), three biostimulant formulations (Cystoseira tamariscifolia L. extract; a commercial legume-derived protein hydrolysate, “Dynamic”; and Spirulina platensis extract) plus an untreated control, and three crop cycles (autumn, autumn–winter, and winter) on leaf yield and dry matter, organic acids, colorimetric parameters, hydrophilic and lipophilic antioxidant activities, nitrate concentration, nitrogen use efficiency, and mineral composition, using a split plot design with three replicates. Protein hydrolysate significantly enhanced yield and nitrogen use efficiency in Mars (+26%), Naples (+25.6%), Tricia (+25%), and Olivetta (+26%) compared to the control, while Spirulina platensis increased the mentioned parameters only in Venice (+36.2%). Nitrate accumulation was reduced by biostimulant application just in Venice, indicating genotype-dependent nitrogen metabolism responses. The findings of the present research demonstrate that the biostimulant efficacy in perennial wall rocket is mainly ruled by genotypic factors, and the appropriate combinations between the two mentioned experimental factors allow for optimization of leaf yield and quality while maintaining nitrate concentration under the regulation thresholds.